Study of Institutional Evaluation in Drainage System Management of Semarang as Delta City - Henny Pratiwi Adi; S. Imam Wahyudi (International Conference on Coastal and Delta Areas, 2015)
Semarang City is one of the cities located in deltaareas. Semarang face problems that always floods inundated parts of the city in every year. Flooding is caused by several things including the change in land use, intensity and high rainfall, erosion and sedimentation in the river channel, decreasing the capacity of the river, building damage flood control, and planning control systems are less precise. Efforts to control the flooding has been done, but more important is how big investmentcan operate and be managed according to plan is to deal with the flooding problem. Therefore, studies are needed to evaluate the management of the drainage system in Semarang city. The data obtained in this study through the literature and the parties related to the management of drainage in Semarang. Literature study conducted to evaluate institutional managers drainage system Semarang. The aspect covered are institution aspect,regulatory aspects, financing aspects, community participation aspect and technical and operation aspects. The results showed that depend on institutions aspect, the existing institutional model is still using the drainage system management by the government, where this management model is facing manyobstacles, especially in terms of financing. Therefore we need a model institution that can improve community participationactively in the management of drainage sytem of Semarang.